2008
DOI: 10.1209/0295-5075/84/37010
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state properties of fermionic mixtures with mass imbalance in optical lattices

Abstract: Ground-state properties of fermionic mixtures confined in a one-dimensional optical lattice are studied numerically within the spinless Falicov-Kimball model with a harmonic trap. A number of remarkable results are found. (i) At low particle filling the system exhibits the phase separation with heavy atoms in the center of the trap and light atoms in the surrounding regions.(ii) Mott-insulating phases always coexist with metallic phases. (iii) Atomicdensity waves are observed in the insulating regions for all … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…On the other hand, the regions of the atomic-density waves retain an insulating character also near half filling. Thus, in accordance with results obtained for the repulsive Falicov-Kimball model [15] we also find that in the attractive FalicovKimball model insulating domains coexist with metallic regions, such that global quantities are not appropriate to describe the system. With an even higher filling, the metallic phase in the center of the trap is further stabilized, but at some critical filling (N = 90) a new insulating phase ("a band insulator") starts to develop in the center of the trap ( = 1 = 1).…”
Section: One-dimensional Casesupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, the regions of the atomic-density waves retain an insulating character also near half filling. Thus, in accordance with results obtained for the repulsive Falicov-Kimball model [15] we also find that in the attractive FalicovKimball model insulating domains coexist with metallic regions, such that global quantities are not appropriate to describe the system. With an even higher filling, the metallic phase in the center of the trap is further stabilized, but at some critical filling (N = 90) a new insulating phase ("a band insulator") starts to develop in the center of the trap ( = 1 = 1).…”
Section: One-dimensional Casesupporting
confidence: 89%
“…The last term is the energy of light and heavy atoms in the harmonic trapping potential of a strength V (for light atoms) and V (for heavy atoms). Very recently, we have performed exhaustive numerical studies of this model for repulsive interactions U > 0 and the same form of the trapping potential for both species of atoms [15]. We have found that the system exhibits the phase separation at low particle fillings.…”
Section: Introductionmentioning
confidence: 99%
“…Cases away from half filling were also studied in Refs. [23,24]. Furthermore, exact diagonalization studies have addressed harmonically trapped systems of up to 10 particles [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The Falicov-Kimball model has been successfully applied to a simplified description of correlation-induced metalinsulator 7,8 and valence-change 9 transitions in rare-earth compounds, or atoms in optical lattices. 10,11 The disordered Anderson model has been used to describe the spectral and transport properties of metallic alloys 12 and vanishing of diffusion, called Anderson localization. 13 There have been efforts to describe the combined effect of electron correlations and randomness in the disordered Falicov-Kimball model 6 or Anderson localization in FKM.…”
Section: Introductionmentioning
confidence: 99%